GK-1 Improves the Immune Response Induced by Bone Marrow Dendritic Cells Loaded with MAGE-AX in Mice with Melanoma - Gabriela Piñón-Zárate; Miguel Ángel Herrera-Enríquez; Beatriz Hernández-Téllez; Katia Jarquín-Yáñez; Andrés Eliú Castell-Rodríguez (Journal of Immunology Research)
The aim of dendritic cell (DC) vaccination in cancer is to induce tumor-specific effector T cells that may reduce and control tumor mass. Immunostimulants that could drive a desired immune response are necessary to be found in order to generate a long lasting tumor immune response. GK-1 peptide, derived from Taenia crassiceps, induces not only increase in TNFα, IFNγ, and MCP-1 production in cocultures of DCs and T lymphocytes but also immunological protection against influenza virus. Moreover, the aim of this investigation is the use of GK-1 as a bone marrow DCs (BMDCs) immunostimulant targeted with MAGE antigen; thus, BMDC may be used as immunotherapy against murine melanoma. GK-1 induced in BMDCs a meaningful increment of CD86 and IL-12. In addition, the use of BMDCs TNFα/GK-1/MAGE-AX induced the highest survival and the smallest tumors in mice. Besides, the treatment helped to increase CD8 lymphocytes levels and to produce IFNγ in lymph nodes. Moreover, the histopathological analysis showed that BMDCs treated with GK-1/TNFα and loaded with MAGE-AX induced the apparition of more apoptotic and necrotic areas in tumors than in mice without treatment. These results highlight the properties of GK-1 as an immunostimulant of DCs and suggest as a potential candidate the use of this immunotherapy against cancer disease.